Analisa Stabilitas Lereng dan Penanggulangan Kelongsoran Lereng Pada Ruas Jalan Batas Kota Liwa-Simpang Gunung Kemala, Taman Nasional Bukit Barisan Selatan, Lampung Barat - arbenta, hermawan; setyanto, setyanto; iswan, iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Landslide are one of the natural disasters that often occur during the rainy season. As in the area of Bukit Barisan Selatan National Park, Lampung Barat, which is a road that is always passed many vehicles. This happens because of an increase in pore water pressure on the slope, which then resulted in a decrease in shear strength (c) and friction angle (φ). Required slope stability analysis and prevention of sliding slopes experiencing.One of the slope stability analysis method used is Fellenius with countermeasures using retaining wall. Fellenius slope stability analysis method (1927) considers the forces that work on either side of any resultant slices have a zero in the direction perpendicular field of avalanche. Fellenius method provides a safe factor is relatively lower than a matter of a more thorough way.From the analysis of slope stability, slope expressed in critical condition. Countermeasures sliding slope using stone retaining wall plug and using gabion. Dimensions and gabion retaining wall that has been planned can be applied in the field so that avalanches do not occur again. Keywords: slope stability, safety factor, fellenius, retaining wall, gabion.